John Amos Comenius - the Teacher of Nations and the Founder of Didactic Principles - Krulj, Jelena R.; Vidosavljević, Slađana T.; Mladenović, Nataša R. (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
The origin of didactics as a science discipline dates from as far back as the ancient slave states, so the very term didactics (didaskein) comes from the ancient Greek language, meaning to teach. This term later underwent certain changes and the term didactica (didactics) originated in Latin. Today, all scientific vocabulary comes from these two languages (Latin and Greek). The first, more precise definition of this concept was given by Wolfgang Ratke (1571–1635) and John Amos Comenius (1592–1670), who are also considered the founders of didactics. The aim of this paper is to emphasize the importance of didactic principles and the great importance and contribution of Comenius as their founder and the founder of didactics in general. We have to mention that Comenius dedicated his entire life and work to the search for the overall improvement of the teaching process and the education of people, and how successful he was can be seen in the factthat his didactic principles still stand the test of time. He is considered to be one of the greatest educational reformers.